Les Episodes D’afflux Massifs De Capitaux Et La Probabilite Des Crises Bancaires et Des Crises De Change - Rechache, Abbassia (المركز الجامعي عبدالحفيظ بوالصوف ميلة - معهد العلوم الاقتصادية والتجارية وعلوم التسيير, 2017)
The purpose of this study is to examine empirically the relationship between large capital inflows episodes and the likelihood of banking and currency crisis, on a panel of 18 emerging countries and 20 developed countries separately, from 1970 to 2010, by Probit and Logit estimation, under the Eviews 9 software. The results show that only in emerging countries, large capital inflows episodes are one of the main drivers of banking and currency crises as they considerably increase the likelihood of these crisis in the two following years.
Keywords: السياسة النقدية -- أسعار الصرف -- العملات الأجنبية